Body fat distribution in the Finnish population: environmental determinants and predictive power for cardiovascular risk factor levels. Issue 2 (June 1991) - Marti, B; Tuomilehto, J; Salomaa, V; Kartovaara, L; Korhonen, H J; Pietinen, P
Abstract : STUDY OBJECTIVE--The aim was to examine (1) whether health habits are associated with body fat distribution, as measured by the waist/hip girth ratio, and (2) to what extent environmental factors, including anthropometric characteristics, explain the variability in levels of cardiovascular risk factors. DESIGN--The study was a population based cross sectional survey, conducted in the spring of 1987 as a part of an international research project on cardiovascular epidemiology. SETTING--The survey was conducted in three geographical areas of eastern and south western Finland. SUBJECTS--2526 men and 2756 women aged 25-64 years took part in the study, corresponding to a survey participation rate of 82%. MEASUREMENTS AND MAIN RESULTS--In men, waist/hip ratio showed stronger associations with exercise (Pearson's r = -0.24), resting heart rate (r = 0.10), alcohol consumption (r = 0.07), smoking (r = 0.05), and education (r = -0.23) than did body mass index. Jointly, exercise, resting heart rate, alcohol consumption, education, and age explained 18% of variance in male waist/hip ratio, but only 9% of variance in male body mass index. In women, environmental factors were more predictive for body mass index than for waist/hip ratio, with age and education being the strongest determinants. Waist/hip ratio and body mass index were approximately equally strong predictors of cardiovascular risk factor levels. The additional predictive power of waist/hip ratio over and above body mass index was tested in a hierarchical, stepwise regression. In this conservative type of analysis the increase in explained variance uniquely attributable to waist/hip ratio was 2-3% for female and 1-2% for male lipoprotein levels, and less than 0.5% for female and 0-2% for male blood pressure values. CONCLUSIONS--The distribution of abdominal obesity in Finland is significantly influenced by health habits and sociodemographic factors in both men and women. This in turn is obviously one reason for the relatively small "independent" effect of body fat distribution on cardiovascular risk factor levels.